Rooted in Landscape: Exploring Place and Identity in Tim Winton’s Novels - Thilaga, P. Josephine Stella; Frederick, Suresh (Journal of Ecohumanism, 2024)
Tim Winton’s novels although his characters may be seen to change shape according to the particular environment that surrounds them. How landscape and place can be seen as backdrop for the construction of identity is the main theme of this article Imbued with a detailed analysis of key works such as Cloudstreet, Dirt Music and Breath, this study examines how Winton’s distinctive Australian settings act as powerful catalysts for internal change and ecological enlightenment. By situating his narrative at once within eco-literature and the Australian literary tradition, the paper invites readers to ponder the intertwining relationship between humankind and nature as well as what sort of ethical duty we owe to it. To summarize, Winton’s work presents an even deeper sense of how place has shaped new form both individual and collective for there is a more responsible approach to environmental issues ahead.